Changing practice patterns in European cataract surgery as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery 2008 to 2017. Issue 3 (March 2021) - Lundström, Mats; Dickman, Mor; Henry, Ype; Manning, Sonia; Rosen, Paul; Tassignon, Marie-José; Young, David; Behndig, Anders; Stenevi, Ulf
Abstract : Preoperative, surgical, and outcomes data from more than 2.7 million cataract extractions reported over a decade to the European Registry of Quality Outcomes for Cataract and Refractive Surgery are described. Abstract : Purpose: To study practice patterns in European cataract surgery over a 10-year period. Setting: European clinics affiliated to the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). Design: Registry cohort study. Methods: The EUREQUO contains preoperative, intraoperative, and postoperative parameters reported by surgeons in many European clinics. All data reported to the registry are anonymized. Preoperative parameters included age, sex, visual acuity, target refraction, ocular comorbidity, and surgical difficulties. Surgical data included anesthesia, surgical technique, intraocular lens optic biomaterial, and complications. Postoperative parameters included visual acuity, refraction, and short-term complications. Results: During the study period (January 1, 2008, to December 31, 2017), a total of 2 714 108 cataract extractions were reported to the EUREQUO. Preoperative data changed over time, with decreases in mean age (74.5–73.0 years), proportion of women from 60.6% (100 373/165 628) to 57.2% (174 908/305 845), and proportion of coexisting eye diseases from 30.0% (49 638/165 650) to 27.0% (82 704/305 846) and with improvements in preoperative visual acuity (mean logarithm of minimum angle of resolution [logMAR] 0.46 to 0.37). The use of topical anesthesia increased over time from 28.1% (26 238/93 320) to 71.7% (130 525/182 083). Surgical complications showed a significant decrease from 2.5% (4107/165 650) to 1.2% (3573/305 846). The visual outcome improved over time (mean logMAR 0.08 to 0.05), as did the absolute median prediction error (0.38 diopter [D] to 0.28 D). Conclusions: Trends in European cataract surgery practice patterns from 2008 to 2017 have moved toward younger patients with better preoperative visual acuity, fewer surgical complications, and better predicted refractions and visual outcomes.